On Making Mandarin a Language of Wider Communication in ASEAN: What Can We Learn from Our Past Experience - NEO Peng Fu (Sinolingua: Journal of Chinese Studies, 2025)
Over the last two decades, in many of the countries in Southeast Asia, there has been an exponential growth among their populace an interest in learning Mandarin, the standard form of the modern Chinese language. The reason is mainly due to a deepening of economic ties between China and the 10-nation bloc of political and economic union called ASEAN (Association of Southeast Asian Nations). Although the various Southeast Asian states each has their own national language, they have adopted English, a non-native language of the region, as the working language of ASEAN. As a matter of fact, English is an inter-national lingua franca in Southeast Asia. This, of course, is a result of the global political and economic developments that have taken place over the several decades after the Second World War. In view of the recent economic and technological rise of China on a global scale, and the strengthening of economic relations between China and ASEAN, will the Chinese language become another language of wide communication in Southeast Asia? This paper aims to answer the question by first taking a look at the spread of English in Southeast Asia, and through which understand the prospects and challenges of making Chinese a language of wider communication in ASEAN.